1976
DOI: 10.1113/jphysiol.1976.sp011365
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of blood flow between individual muscles and non‐muscular tissues in the hind limb of the young ox (Bos taurus): values at thermoneurality and during exposuer to cold.

Abstract: SUMMARY1. The radioactive microspheres method was used to measure the distribution of blood flow in the hind leg in conscious young steers exposed to thermoneutral and moderately cold environments. Simultaneous measurement of total leg blood flow allowed calculation of blood flow (ml. 100 g tissue-' min-') to individual muscles and the major non-muscular tissues in the leg.2. In the thermoneutral environment, leg blood flow was distributed approximately according to tissue weight, so that about 65 % went to mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…This conclusion agrees with previous physiologic studies that indicate functionally parallel circulations to these two tissues [4]. Microspheres have been used to measure blood flow in bone [5][6][7][8][9][10][11] or as part of a larger project [12][13][14][15] without knowledge of marrow-bone relationships, effects of catheter siting or positioning of the dog, or percentage of entrapment of microspheres.…”
Section: Introductionsupporting
confidence: 86%
“…This conclusion agrees with previous physiologic studies that indicate functionally parallel circulations to these two tissues [4]. Microspheres have been used to measure blood flow in bone [5][6][7][8][9][10][11] or as part of a larger project [12][13][14][15] without knowledge of marrow-bone relationships, effects of catheter siting or positioning of the dog, or percentage of entrapment of microspheres.…”
Section: Introductionsupporting
confidence: 86%
“…after milking, changing from less than 0.5 to over 2.0 L/min. In another study, Bell et al (1976) found that the blood supply to the hind limb increased during shivering. However, the blood supply to the leg skin decreased substantially in both total and capillary blood flow.…”
Section: Discussionmentioning
confidence: 96%
“…The catheter in the deep femoral vein was inserted, via the lateral saphenous vein, so the tip was located adjacent to the pelvic symphysis (c. 70 cm from the junction of the caudal and cranial branches of the lateral saphenous vein). This catheter was located in a position to allow collection of blood draining predominantly muscle tissue (see Bell et al 1976), whereas the catheter in the mammary vein allowed collection of mixed mammary venous blood. Catheters were filled with sterile heparinized saline (2'5 x 10 5 i.u.…”
Section: Surgical Preparationmentioning
confidence: 99%